PENGEMBANGAN PROTOTIPE SMART CONTRACT BERBASIS BLOCKCHAIN UNTUK TRACEABILITY RANTAI PASOK TEH PUTIH DI PPTK GAMBUNG - Yulinar, Irna; Indah Mega Mandasari, Rizza; Agung, Anak Agung Gde; Nurbudyana, Nanda Harry; Dillak, Rixard George; Saputra, Arya Rangga Dwi; Jannah, Salma Nida Ul; Tanjaya, Ivan (LPPM Universitas Bina Bangsa, 2025)
Pusat Penelitian Teh dan Kina (PPTK) Gambung is a research institution that focuses on tea and quinine commodities. PPTK Gambung intends to create a blockchain-based traceability system for the tea supply chain to improve transparency and product quality. Blockchain technology enables secure, immutable, and transparent data recording so consumers can easily trace the origin of products. There has previously been development of a traceability system for green tea that helps ensure that tea products meet ethical and environmental standards. However, to expand the reach and meet partner demand, developing a similar traceability system for white tea is important. White tea is one of the leading products due to its high polyphenol content, which has various health benefits. With this system in place, the white tea supply chain process is expected to be managed with the same transparency, ensuring that the product is not only high quality but also ethically and sustainably produced. This problem will be solved through the proposed community service activity. Through this community service activity, PPTK Gambung can have a smart contract prototype that can be used as a pilot to be submitted to the national level.